EMAIL AS A MEDIA IN TEACHING ENGLISH TO IMPROVE STUDENTS 'WRITING ABILITY IN SMP NEGERI 1 MADANG SUKU III OKUT - Nurul Afifah (STKIP PGRI Lubuklinggau, 2018)
Writing is one of the must-have skills when learning a language. Likewise with English, there are 4 skills in English that must be owned that is writing, listening, reading and speaking. Writing is a process of creating, developing, composing ideas using written language. In this research, there are 2 objectives: 1) to know whether writing ability in English subjects by using email is better than conventional learning student 2) to know whether students show positive attitude toward learning English using Email. This research uses quasi experimental method and design of non-equivalent control design. In this design gives two different treatments to two groups namely experiment class and control class. The experimental class and control class were given pretest before treatment, then for control class was done by conventional learning, after experiment class and control class were given each treatment and then given the final test (posttest) in both classes. The results of this study are 1) the ability to write English students whose learning using email better than students who learning conventional2) Students showed a positive attitude towards learning using email.